Effect of tannin from blackberry (Syzigium cumini) seed on in vitro rumen fermentation - Barma, SCK; Amin, MR; Monirruzzaman, M; Sarker, MB; Kabir, AKMA (Progressive Agriculture, 2015)
An experiment was conducted to quantify the chemical composition, different forms of tannins and their effects on in vitro gas production, organic matter digestibility and metabolisable energy content in Syzigium cumini (Blackberry) seed with and without polyethelene glycol (PEG). The DM, OM, ash, CP, NDF and ADF contents of S. cumini seeds were 90.1, 87.6, 2.6, 4.6, 32.9 and 15.5%, respectively. The total phenol, total tannin, condensed tannin and hydrolysable tannin content were 5.89, 4.25, 0.42 and 0.05mg/g seed, respectively. In vitro gas production, organic matter digestibility and metabolisable energy content of S. cumini seed were 54 ml, 42.91% and 6.43 MJ/Kg DM, respectively. Addition of PEG to tannin containing seed was significantly (P<0.05) increased in vitro gas production, OMD and ME content. Higher levels of tannins in S. cumini seed could limit utilization through impaired digestibility and nutrient utilization but the addition of PEG increased all the fermentation parameters studied. It is predictable from the present findings that S. cumini seed could be utilized as natural source of feed additives to alter rumen fermentation parameters especially to protect protein and other nutrients from ruminal degradation, thereby make the nutrients available in the lower tract for higher milk and meat yield. Progress. Agric. 2014. 25: 31-37